2018
DOI: 10.1038/nchem.2926
|View full text |Cite
|
Sign up to set email alerts
|

Endothermic singlet fission is hindered by excimer formation

Abstract: Singlet fission is a process whereby two triplet excitons can be produced from one photon, potentially increasing the efficiency of photovoltaic devices. Endothermic singlet fission is desired for a maximum energy-conversion efficiency, and such systems have been considered to form an excimer-like state with multiexcitonic character prior to the appearance of triplets. However, the role of the excimer as an intermediate has, until now, been unclear. Here we show, using 5,12-bis((triisopropylsilyl)ethynyl)tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
189
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(198 citation statements)
references
References 38 publications
9
189
0
Order By: Relevance
“…38 Dover et al have shown the conversion between monomers and excimers through triplet pair and free diffusion during both singlet fission and TTA-UC. 39 We have further suggested that another main reason for the surprisingly large amount of excimer emission in perylene based photon upconversion is due to a preassembly step on the triplet energy surface, already before the upconversion event. 40 Alkyl substitution offers the opportunity to manipulate the stacking interactions of perylene with minimal impact on the excited levels of the individual molecules.…”
Section: Introductionmentioning
confidence: 84%
“…38 Dover et al have shown the conversion between monomers and excimers through triplet pair and free diffusion during both singlet fission and TTA-UC. 39 We have further suggested that another main reason for the surprisingly large amount of excimer emission in perylene based photon upconversion is due to a preassembly step on the triplet energy surface, already before the upconversion event. 40 Alkyl substitution offers the opportunity to manipulate the stacking interactions of perylene with minimal impact on the excited levels of the individual molecules.…”
Section: Introductionmentioning
confidence: 84%
“…The presence of excimer formation pathways has previously been implicated as deleterious in endothermic SF situations. 57,58 Excimer formation is less likely at low temperature, which is evident from the structured fluorescence and the slowing of the CT decay, from which at least a portion of the excimers arise ( Figure S7). The CT yield can be determined with the aid of the known radical cation extinction coefficients ( Figure S8) to be roughly 20% for 2a, 30% for 2ĂĄ and 40% for 2Ăą at room temperature.…”
Section: Prediction Of Better Packing Geometries the Formation Of Exmentioning
confidence: 99%
“…[1] Therefore,SFcan potentially offset the thermal losses and enhance the maximum power conversion efficiency of photovoltaic devices. [1][2][3] Theenergetic requirement of E(S 1 ) % 2 E(T 1 )by an efficient SF process is not frequently met in most organic molecules.C onsequently,o nly ah andful of molecules are known to fulfil this thermodynamic condition, including tetracene, [4] pentacene, [5] some of their derivatives, [6] perylenediimide, [7] oligoenes, [8] and donor-acceptor polymers. [9] SF has been implemented in photovoltaic device and peak external quantum efficiency above 100 %h as been obtained.…”
mentioning
confidence: 99%